Impact of COVID-19 on Pakistani dentists: a nationwide cross sectional study - Ramsha Kamran; Kiran Saba; Saima Azam (BMC, 2021)
Abstract Background The COVID-19 outbreak which developed into a public health crisis has raised concerns regarding infection control among health care workers particularly dentists all over the world. The aim of this survey was to assess awareness, fear and compliance with practice modification according to CDC guidelines during COVID-19 pandemic among Pakistani dentists. Methods A cross-sectional study was conducted using an online survey questionnaire. The questionnaire was designed on Google Forms and was distributed among all seven regions of Pakistan through social media and WhatsApp after carrying out the reliability analysis. Statistical analysis was performed using SPSS 20.0. Question wise analysis using frequencies and percentages was done. Pearson correlation and Kruskal Wallis test was applied to check association of awareness level with qualification and workplace setting. Results A total of 313 dentists participated and submitted the form online from all regions of Pakistan. The response rate was quite satisfactory as Pakistan was under an official lockdown and most of the hospitals/clinics were either closed or operating with minimum staff. Most of the dentists were well aware of the CDC guidelines. However, 75% of the dentists were afraid of getting infected and 88% of them were anxious while providing treatment. Sixty-eight percent of them were avoiding aerosol generating procedures and only 28% were using rubber dam isolation. Regional analysis was also done and areas of poor compliance were identified. Only 38.5% dentists in Balochistan were using N95 masks and none of the dentists (0%) were using rubber dam isolation. A large number of dentists (80.9%) were afraid and wanted to close their dental practice in Khyber Pakhtunkhwa. Furthermore, a positive correlation was seen between the designation and awareness level (p = 0.01). Similarly, significant correlation (p = 0.03) was seen between qualification and workplace setting. Conclusion The results of the study can help devise strategies to ensure adherence with infection control guidelines in regions with poor compliance. Initiation of awareness programs to help overcome fear and train the faculty and staff in the targeted areas would greatly contribute towards reducing the spread of infection and thus lowering the healthcare burden in a third world country like Pakistan.